Developing Employee Resilience: The Role of Leader-Facilitated Emotion Management. Issue 4 (November 2020) - Richard, Erin M.
The Problem: To create resilient organizations, Human Resource Development (HRD) must foster the conditions (both internal and external to the employee) that enable learning and development in the face of adversity. Yet the experience of adversity produces intense negative emotions that threaten learning and development. Resilience building programs typically focus on building resources internal to the worker (e.g., self-efficacy, optimism) as a means of buffering against the negative effects of future stressors, but considerably less focus is placed on supporting others in their attempts to cope. Additionally, the role of leadership in promoting follower resilience has received limited attention. The Solution: This article begins by summarizing the role of emotion and emotion regulation in recent literature on employee resilience. Toward that goal, a literature search was conducted for reviews and theoretical models of employee resilience published in peer-reviewed journals over the past 10 years. Next, emerging scholarship on interpersonal emotion management (IEM) is introduced, with a focus on its application in work and leadership contexts. The argument is made that leaders are in a unique position to promote resilience in their followers, through the promotion of positive emotional states and through the mitigation of the negative emotional states that accompany adversity. As such, developing IEM skills in both resilience training and leadership development programs should increase employee resilience. The Stakeholders: Leaders, scholars, and HRD professionals interested in promoting employee resilience and developing effective leaders will benefit from this application of interpersonal emotion management concepts to the topic of employee resilience.